The association of GSTP1 (A313G), MTHFR (С677Т) and IL-10 (C819T) genes polymorphisms with the glioblastoma risk - Gorbach, Oleksandr; Skachkova, Oksana; Shymon, Daria; Khranovska, Natalia; Glavatskyi , Oleksandr; Zemskova, Oksana (The Ukrainian Scientific Medical Youth Journal, 2023)
glioblastoma is one of the most common malignant brain tumors with an extremely low survival rate. The causes of glioblastoma disease are still unclear. Research in past years showed that genes involved in cell proliferation, differentiation and apoptosis can affect the risk of cancer. The aim was to investigate the distribution of GSTP1(A313G), MTHFR (C677T) and IL-10 (C819T) gene polymorphisms in patients with glioblastoma and to analyze their association with the glioblastoma risk. For the GSTP1, MTHFR and IL-10 gene polymorphism analysis was used the peripheral blood of patients with glioblastoma and practically healthy people. The gene polymorphism detection was carried by allele-specific PCR using specific pairs of TaqMan MGB detectors. The frequency of the mutant G allele in GSTP1 gene in patients was 53.6% compared to 32.0% in the group of healthy people was established. The GSTP1 genotype distribution was corresponded to the Hardy-Weinberg principle in the group of patients and was statistically different in the group of healthy people (0.538 versus 0.320 respectively, χ2 = 13.10, p = 0.003). The risk of glioblastoma is 4.88 times higher in mutant homozygous variant GSTP1 gene (genotype G313G) compared to other polymorphic variants was established. According to our research, the mutant C allele frequency in the IL-10 gene was 48.8% than higher in healthy group (frequency 25%) was evaluated. In addition, the IL-10 genotype distribution was corresponded to the Hardy-Weinberg principle in the group of patients and was statistically different in the group of healthy people (0.488 versus 0.250 respectively, χ2 = 18.32, p = 0.00002). We established the association between the polymorphism IL-10 (C819T) and glioblastoma risk. Namely, the presence of mutant IL-10 gene (T819T) variant increased in 6.40 times the glioblastoma risk compared to other polymorphic variants (χ2 = 17,17, p = 0,0002). We also established that, the mutant T allele frequency of the MTHFR gene (C677T) was 35.0% versus 28.1% in the group of healthy people. The MTHFR genotype distribution was corresponded to the Hardy-Weinberg principle in the group of patients and wasn’t statistically different in the group of healthy people (χ2 = 1.43, p = 0.23). The association of MTHFR gene polymorphism (C677T) and glioblastoma risk wasn't established.